An evaluation of pink salmon (Oncorhynchus gorbuscha) testes meal in diets for pacific white shrimp (Litopenaeus vannamei): effect on palatability, digestibility and growth performance. (19th February 2013) - Deng, D.F.; Ju, Z.Y.; Dominy, W.G.; Bechtel, P.J.; Smiley, S.
Abstract This study compared the nutritional profiles of menhaden fishmeal and pink salmon (Oncorhynchus gorbuscha) testes meal and investigated the nutritional values of the testes meal based on its effect on palatability, digestibility and growth performance of Pacific white shrimp (Litopenaeus vannamei). The testes meal replaced 0–91% of fishmeal protein in a control diet containing 150 g kg−1 fishmeal. Replacement of 69% of the fishmeal protein in the control diet significantly increased feed intake of shrimp from 0.61% to 1.10%. The apparent digestibility coefficient of dietary protein increased significantly when 91% of the fishmeal protein was replaced by the testes meal. Replacement of dietary fishmeal protein with up to 46% testes meal protein did not cause adverse effects on growth rate or nutritional composition of tail muscle. However, growth rate was significantly decreased in shrimp fed diets in which 69% or 91% of fishmeal protein was replaced by the testes meal. Results of this study indicate that the testes meal can be used as a feed additive to enhance the palatability and protein digestibility of low fishmeal diets for shrimp. It can replace up to 46% of fishmeal protein without any adverse effect on the growth performance of shrimp.